Effect of Annealing on Optical Properties of ZnO·LiF·B2O3 Glasses. (18th October 2012) - Arora, Susheel; Kundu, Virender; Goyal, D. R.; Maan, A. S.
Abstract : The Melt-quench method is used to synthesize zinc fluoroborate glasses with compositions x Z n O · ( 40 − x ) L i F · 60 B 2 O 3 (x = 0, 5, 10, 15, and 20). Optical characterization was carried out to examine the variation of optical bandgap energy (E g ) and urbach energy (E U ) with respect to the concentration for the samples annealed at different temperatures (300 ° C, 350 ° C, and 400 ° C ). Annealing shows its effect on the samples with the variations in the values of E g and E U . These variations are explained on the basis of formation of different molecular species like BO 3 - units, boroxol rings, and the change in the number of nonbridging oxygen atoms.